Acute psychoses: An unusual presentation of empty sella syndrome - Abhishek Singhai; Karan Kapur; Sagar Khadanga; Aparna Paramanandam (Wolters Kluwer Medknow Publications, 2019)
We report a case of a 54-year-old female admitted to our hospital with altered behavior. We found that severe hyponatremia (116 mEq/L) was the cause of the patient's status. In turn, hyponatremia was due to panhypopituitarism. Mild-to-moderate hyponatremia had been previously detected in this patient; however, it was overlooked. The clinical onset of panhypopituitarism is often characterized by mild nonspecific symptoms, especially in the older people, and it is often overlooked. Although hyponatremia is a common electrolyte disorder in the elderly, physicians should not forget that it could be the leading manifestation of panhypopituitarism. Panhypopituitarism may be easily diagnosed; however, clinical suspicion is needed. Due to the high mortality associated with panhypopituitarism, hormone assays should be included in the initial diagnostic workup of hyponatremia.